I can draw machines - Love, Carrie; Mack, Lorrie; Crawford, Andy; Peter Bull Art Studio (New York, NY : DK Pub., 2006)
Juvenile works
Useful stuff -- Photo gallery -- Sports car -- Race car -- More car ideas -- Airplane -- Stealth bomber -- Hide or highlight? -- Shading -- Backhoe -- Roller -- Dumptruck -- Tractor -- Look out! -- Helicopter -- High-speed train -- Texture -- Motorcycle -- Speedboat -- Monster truck -- Watch me! -- Scale.
Includes index.
Keywords: Vehicles in art -- Juvenile literature; Drawing -- Technique -- Juvenile literature